2009
DOI: 10.2807/ese.14.33.19311-en
|View full text |Cite
|
Sign up to set email alerts
|

The importance of school and social activities in the transmission of influenza A(H1N1)v: England, April – June 2009

Abstract: During the containment phase in the United Kingdom (April to June 2009), a cluster of influenza A(H1N1)v cases was identified prompting further investigation and public health action by the Health Protection Agency. The first confirmed case, a pupil at a school in England, was imported. During the following two weeks, 16 further cases were confirmed with epidemiological links to the first imported case. In this cluster, we found that significant transmission occurred in two classes with attack rates of 17% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 4 publications
(5 reference statements)
2
40
0
Order By: Relevance
“…Stratification based on whether the subjects' family included students attending school at that period showed an increase in the pandemic H1N1 infection rate in the families that had school children. This clearly suggested that school children should be one of the key target populations for vaccination to pursue infection control, and this view is shared by an English research group, which highlighted the importance in protecting school children during the pandemic (Kar-Purkayastha et al, 2009). Our data also show that medical personnel with asymptomatic infection with pandemic H1N1 may be a risk factor for hospital-onset infection in Beijing.…”
Section: Discussionsupporting
confidence: 47%
“…Stratification based on whether the subjects' family included students attending school at that period showed an increase in the pandemic H1N1 infection rate in the families that had school children. This clearly suggested that school children should be one of the key target populations for vaccination to pursue infection control, and this view is shared by an English research group, which highlighted the importance in protecting school children during the pandemic (Kar-Purkayastha et al, 2009). Our data also show that medical personnel with asymptomatic infection with pandemic H1N1 may be a risk factor for hospital-onset infection in Beijing.…”
Section: Discussionsupporting
confidence: 47%
“…This may be explained by the differential pattern of virus transmissions in each region in view of the variation of population structures, or that there were higher uptake of reported cases in some locations against the background of considerable public attention, when the news of an impending epidemic first broke out[7]. On the other hand, the landscape of the epidemic curve thus constructed was contributed largely by infections in students, an observation made in other studies on pandemic (H1N1) as well as seasonal influenza[8,9]. Against the background of a relatively uniform physical and climatic environment within Hong Kong, the temporo-spatial variability of influenza spread could only be explained by the heterogeneous population structure and mobility patterns.…”
Section: Resultsmentioning
confidence: 99%
“…An interesting observation was that the outbreak occurred in November as opposed to April to June as noted in other reports. [4][5][6][9][10][11] An outbreak was noted in Saudi Arabia in the month of October as well.…”
Section: Resultsmentioning
confidence: 99%